An Occupation and Participation Approach to Reading Intervention (OPARI) part I: Defining reading as an occupation. Issue 1 (2nd January 2016) - Grajo, Lenin C.; Candler, Catherine
ABSTRACT: This is the first of two papers that explore a role that occupational therapy can play in supporting children with reading challenges. Part I presents the grounding framework for an occupation and participation approach to reading intervention (OPARI) and serves to introduce the clinical application of the approach presented in Part II. In this paper, reading is defined as an occupation in daily life. Different perspectives in occupational therapy, education, cognitive psychology and cognitive neuroscience were examined to support a holistic, participation approach to reading. The Occupational Adaptation model (Schkade & Schultz, 2003) is proposed as a guiding framework to describe the assumptions and premises of the OPARI. Lastly, the five essential components of the OPARI are identified as a basis for how the OPARI may be applied in clinical practice.